2013
DOI: 10.1136/ejhpharm-2013-000276.399
|View full text |Cite
|
Sign up to set email alerts
|

OHP-025 Drug Information and the Use of a Pillbox to Improve Satisfaction of Patients Treated with Temozolomide

Abstract: Background Compliance is sometimes difficult for patients treated with temozolomide, because of the inconvenience due to the high daily number of capsules needed. Studies with other drugs showed that pillboxes increased patient satisfaction. Purpose To determine if pharmaceutical information and the use of pillboxes may improve satisfaction of patients treated with temozolomide. Materials and Methods This prospective and interventional study included adult patients who picked temozolomide up in our Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In this way, one can observe that the pillboxes are a simple, low-cost way to intervene in difficult to adhere to a drug treatment, but that still requires further studies in relation to the difficulties presented by the older adults while using them [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this way, one can observe that the pillboxes are a simple, low-cost way to intervene in difficult to adhere to a drug treatment, but that still requires further studies in relation to the difficulties presented by the older adults while using them [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that seniors' ability to take oral prescription drugs safely is affected by cogni-tive function and socioeconomic status [2,26], health knowledge, and health and medication habits [8,27]. In addition, studies have suggested that special attention should be paid to persons taking three or more drugs, living alone, and receiving drugs from multiple doctors, as well as to those with pre-dementia symptoms, as they are at higher risk of non-adherence [2,21,25,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations